When Narcissus Became a CEO: CEO Narcissism and Its Effect on Earnings Management - Patricia Gabriela Christian; Dedhy Sulistiawan (Jurnal Dinamika Akuntansi dan Bisnis, 2022)
This  study  examines  the  role  of  CEO  narcissism  to  earnings  management.  Samples  are non-financial companies listed in  Indonesian  Stock  Exchange.  Three indicators are  used  to reflect the CEO's  narcissistic  nature:  CEO  photograph,  CEO  publicity,  and  CEO's social  media. Overall, the principal component analysis of the narcissism variable is not able  to  explain  earnings  management.  After  splitting  the  indicators,  the  results  show empirical  evidence  that  CEO  publicity  affects  earnings management.  This  study  also documented  that  CEO  publicity  stimulates  earnings  management  for  firms  with  more profitability. These findings contribute  to  earnings  management  literature  by  providing  evidence  that  profitability positively  affects  earnings  management,  especially  for firms with  higher CEO narcissism measured by CEO publicity.